Mechanical properties and micro-mechanisms of soft soil stabilized with rice husk ash and multi-source solid waste-based cementitious materials - Xu, Rui; Xie, Yuxiang; Chen, Yichao; Li, Zhenya (Frontiers in Built Environment, 2026)
To address the issues of high energy consumption, significant carbon emissions, and suboptimal effectiveness associated with conventional cement-stabilized soft soil, this study proposes a novel binder composed of rice husk ash (RHA) and multi-source solid wastes for soft soil stabilization. Unconfined compressive strength (UCS) tests and scanning electron microscopy (SEM) were conducted to investigate the mechanical properties and micro-mechanisms of this composite stabilization system. The results indicate that: (1) For the composite stabilized soil across all curing ages, the order of significance of the factors influencing strength is RHA content > carbide slag content > cement-to-ground granulated blast furnace slag (GGBS) ratio. The optimal binder composition, based on UCS evaluation, is RHA:cement:GGBS:carbide slag = 3:6.4:9.6:1 when the mass ratio of composite binder to dry soil is 20%. (2) Compared to cement-stabilized soil with the same binder content, the optimal composite stabilized soil exhibited 24% and 39% higher UCS at 14 and 28 days, respectively. The stress-strain curves shifted rightward, with increased ultimate strain and enhanced toughness. (3) SEM analysis revealed significantly more dense honeycomb and network structures in the composite stabilized soil compared to cement-stabilized soil. Hydration-generated calcium silicate hydrate (C-S-H) gels connected and filled the pores, improving soil density and strength.